Self Names in The Mula Tau Text - Hunaeni; M. Dalyan; Ashima Cakka Mayura (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Mula Tau episode as a part of the text of La Galigo, is a masterpiece of Bugis literature that has begun to be marginalized by millennials in Buloé, South Sulawesi. The uniqueness of the episode lies in the similarity of some of its parts to the dynamics of other ethnic texts in Indonesia. For example, on the role of the agent structure as the driving force of a literary work. It is these agents who with their respective roles have built a system of literary works. As the energy of a literary work, they are marked with their names according to their respective characters and roles. In simple terms, understanding the self-name can also be used as the key to understanding the storyline, it can even show the outlines of the cosmological view and the cosmogony of the Bugis autochthon. This study focuses on library research considering that the object of the study is in the form of documents. However, field research is still needed to translate and obtain a recording of the reading of the manuscript for transliteration purposes. The Mula Tau text is written in lontarak script. It's read as a literal Bugis language, so the self-name data collection begins with a translation; structuring sentence patterns, and identifying linguistic units that precede a name. Furthermore, the semantic theory used is based on referential theory. Research findings include various self-names and their meanings collected in two types of language styles, namely metaphor and metonymy. Likewise, the findings of self-names with article markers, morphemes, and unsigned ones.